A finite element study on the ultimate lateral drift capacity of interior reinforced concrete flat slab-column connections. (December 2022) - Najafgholipour, M.A.; Sarhadi, F.
Abstract: Reinforced concrete (RC) flat slabs may be a part of the lateral load resisting system or may only serve as a gravity load bearing element in RC structures. In both cases, RC slab-column connections have a crucial role in the global seismic performance of RC buildings. Punching shear failure in flat slabs concentrated in the slab-column connection region is a common brittle failure mode which can adversely affect the global seismic behavior of structures. However, few studies have been done on the numerical simulation of brittle shear failure in slab-column connections under simultaneous gravity and lateral loads. In this paper, to evaluate the behavior of RC slab-column connections under simultaneous gravity and lateral loads and to examine the effects of various influential parameters on the lateral drift capacity of the connections, a numerical study is conducted on interior slab-column connections. The investigated influential variables are the flexural reinforcement in the slab, slab thickness, and the dimensions of the supporting column. The numerical study is implemented in the finite element software ABAQUS. First, the numerical model is verified through modeling three interior RC slab-column connections tested in other experimental studies. Then, all the connections are analyzed under the simultaneous effects of gravity and lateral loads and their lateral load-drift curves are determined. According to the analysis results, in addition to the gravity load intensity, other variables such as flexural reinforcement ratio, slab thickness, and the size of the supporting column affect the lateral behavior of the connection.